The Influence of the Classical Learning Model on Students' Interest in Learning at SMKN 1 Bantaeng - Darwis, Muh.; Fitriah, Nursakinatul; Arhas, Sitti Hardiyanti (Pinisi Journal of Education and Management, 2023)
Teachers or teaching staff play an important role in education. One of the teacher's responsibilities during training is to choose training strategies that are considered most suitable, efficient, and effective for achieving training objectives. To make students interested in training, teachers need to be able to use the right form of training to make the training process more interesting. This research aims to determine the relationship between the use of classical forms of training and the learning interest of class XI OTKP students at SMKN 1 Bantaeng by describing the use of classical forms of learning and students' interest in learning. This research uses descriptive and inferential statistical tools as well as quantitative research methods with associative statistical research types. This research used a simple random sampling method by selecting a sample of 51 people. Questionnaires and documentation were used to collect data. The research results show that both the interest in learning variable (x) and the classical form of training variable (x) have a positive sign. These two variables have a strong relationship with the product-moment correlation test. Judging from the consequences of the basic straight test relapse, it is suspected that there is a positive and large relationship between the old style of training and the learning interest of class XI OTKP students at SMKN 1 Bantaeng. Because previous research focused on methods used to increase students' interest in learning, this research can be used as a reference in its application using classical forms of training in the classroom by paying attention to existing indicators to increase students' interest in learning